Biodiversity of Old-growth Coniferous Forests in the Ural Mountains - Ivanova, Natalya Sergeevna (International Journal of Bio-resource and Stress Management, 2019)
Due to a steadily growing human-induced impact on the biosphere, natural biological diversity preservation and support for forest ecosystems and their dynamics forecast is one of the most urgent global issues. The aim of our research was to identify geographical and landscape diversity features of the mountain forests of the South and the Middle Urals (Russia) based on forest typology, landscape ecology and vegetation science approaches. As a result of the long-term research (1991-2017), quantitative data on biological diversity of old-growth coniferous forests were obtained. Productivity and species saturation of the subordinated layer was studied. It was established that a diversity of forest vegetation conditions and an ecotone effect lead to modern forest type diversity. The research has complemented data on forest types with information on productivity and species saturation for a herb and shrub layer of nominally primary forests. A natural biodiversity level required to preserve natural ecosystem stability was identified. The minimum values are revealed at steep slopes and upper mountains, both in the Southern, and the Middle Urals. The largest species saturation is revealed in lower smooth slopes for moss spruce forests of the Southern Urals and for Multi-herb pine forest of the Middle Urals. The carried-out analysis has shown the advantages for joint use of forest typology, landscape ecology and floristic analysis methods for forest vegetation research. The conducted work forms a scientific basis for biodiversity preservation of the Ural mountain forests, their regional and landscape dynamics research, justified forecast of forest resource conditions.